PENGARUH ORGANIZATIONAL SUPPORT AND EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PADA PT PLN (PERSERO) UNIT LAYANAN PELANGGAN MEDAN DENAI - Nurul Wahyuni; Yayuk Yuliana (Sekolah Tinggi Pariwisata Mataram, 2023)
This study aims to determine the effect of Organizational Support and Employee Engagement on Employee Performance at PT. PLN (Persero) Medan Denai Customer Service Unit. This study uses a quantitative descriptive approach. The population of this study are employees of PT. PLN (Persero) Medan Denai Customer Service Unit, namely 60 employees. The research sample was obtained using the entire population to be used as a sample, namely as many as 60 employees. The analysis technique used is multiple regression analysis. The suitability test using the t test and F test was carried out to test the effect partially and simultaneously between the independent variables and the dependent variable with the assumption that other variables are considered constant. Based on the results of multiple linear regression tests, it is known that the multiple linear regression equation of this study is: Y = 7.182+ 0.380X1 + 0.225X2. The positive equation value indicates that if there is an increase in Organizational Support and Employee Engagement, the Employee Performance will also increase. Based on the results of the F test, the calculated f value is 39,180 with a sig level of 0.000, therefore the sig value is 0.000 > 0.05 and the calculated F value is 39,180 > F table 3.16. This shows that Ho is rejected, so it can be concluded that the independent variables X1 and X2 are significantly simultaneous positive and significant effect on the dependent variable Y. Based on the test results of the coefficient of determination, the Adjusted R Square value is 0.564 or 56.4%. This means that the percentage of Organizational Support (X1) and Employee Engagement (X2) on Employee Performance (Y) is 56.4%, while the remaining 43.6% is influenced by other variables not examined by this study such as motivation, job satisfaction, commitment, loyalty and others.